PERAN PEMERINTAH DAERAH DALAM MEMBERIKAN PERLINDUNGAN HUKUM TERHADAP WISATAWAN DI KABUPATEN SIKKA - Josviranto, Micael (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The Sikka Regency Government plays an important role in providing Legal Protection to Tourists in Sikka Regency. This legal protection causes tourists to feel that they have a tourist location, so tourism in Sikka Regency can develop better. This type of research used in this study is qualitative research in the form of intervie ws and natural observation. Types of Legal Materials are tourism and tourism law as well as Regional Regulation No. 3 of 2017 concerning Tourism Business in Sikka Regency. The results showed that it could create business opportunities. With the arrival of tourists, services are needed to provide for the needs (wants), wants (want), and expectations (expectations) of tourists. Tourism is one of the potential resources to substitute other natural resources such as oil and gas which is declining.